Swedish economic policy - Lindbeck, Assar (London : Macmillan, 1975)
The book is a broadly based, comprehensive analysis of economic policy in Sweden. The emphasis is on the period after the Second World War, though earlier developments are also briefly outlined. It is A revision and extension of the author's Svensk ekonomisk politik, published in 1968.
Includes index.
Includes bibliographical references: p. 253-264.
osc 28/01/2019
Loans
Keywords: Economic policy; Sweden